2020
DOI: 10.1126/sciadv.aaz2433
|View full text |Cite
|
Sign up to set email alerts
|

A hexavalent Coxsackievirus B vaccine is highly immunogenic and has a strong protective capacity in mice and nonhuman primates

Abstract: Coxsackievirus B (CVB) enteroviruses are common human pathogens known to cause severe diseases including myocarditis, chronic dilated cardiomyopathy, and aseptic meningitis. CVBs are also hypothesized to be a causal factor in type 1 diabetes. Vaccines against CVBs are not currently available, and here we describe the generation and preclinical testing of a novel hexavalent vaccine targeting the six known CVB serotypes. We show that the vaccine has an excellent safety profile in murine models and nonhuman prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 44 publications
1
83
0
1
Order By: Relevance
“…Information on cross-reactivity could be important for studying prototype vaccines’ responses, or if aiming to produce more accurate assays by reducing cross-reactivity. In recent years the interest in vaccinating against enteroviruses that cause chronic diseases have gained more momentum and prototype vaccines are being developed [ 34 , 35 ]. One major source of cross-reactivity between enterovirus antibodies is the VP1 N -terminal enterovirus group-specific immunodominant epitope; however, it is not a neutralizing one [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information on cross-reactivity could be important for studying prototype vaccines’ responses, or if aiming to produce more accurate assays by reducing cross-reactivity. In recent years the interest in vaccinating against enteroviruses that cause chronic diseases have gained more momentum and prototype vaccines are being developed [ 34 , 35 ]. One major source of cross-reactivity between enterovirus antibodies is the VP1 N -terminal enterovirus group-specific immunodominant epitope; however, it is not a neutralizing one [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, viral vaccines or anti-viral drugs have never been tested, and now they have become attractive candidates to be studied in clinical prevention trials. In animal models, the vaccine protected mice infected with CVB from developing virus-induced T1D [28]. However, the study using the viral vaccine as preventive therapy has not been conducted in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In these animals, the vaccine-induced antibodies to CVB, suggesting it could protect against the virus. The clinical studies testing the vaccine against CVB in human subjects are on the horizon [28]. The CVB vaccine could be effective for the primary prevention of T1D by halting an induction of beta-cell autoimmunity.…”
Section: Primary Preventionmentioning
confidence: 99%
“…It is suggested that even in a host background prone to autoimmunity, the antiviral defense in β-cells plays a role in preventing VID onset. The Socs-1 Tg NOD mice have been used as a model animal to verify the effects of vaccination [120,121].…”
Section: Socs-1mentioning
confidence: 99%